Participatory action research: A strategy for improving self-care management in chronic obstructive pulmonary disease patients - Padilha, José Miguel Santos Castro (2020)
Submitted by zulmira ribeiro (zulmira@esenf.pt) on 2020-11-09T16:15:20Z No. of bitstreams: 1 artigo afiliado Paulino-04.pdf: 341766 bytes, checksum: ded790fdc651ea99a037653c3fec8152 (MD5)